Pengaruh Penggunaan Aplikasi Wordwall Terhadap Hasil Belajar Matematika Siswa Kota Parepare - Rofinus Badung; Asdar Dollo (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2024)
This study aims to determine the positive effect of using the wordwall on the mathematics learning outcomes of class VIII UPTD SMP Negeri 2 Parepare students. This type of research is quasi-experimental. The population of this research is class VIII UPTD SMP Negeri 2 Parepare for the academic year 2022/2023 which consists of ten classes, namely VIII 1, VIII 2, VIII 3, VIII 4, VIII 5, VIII 6, VIII 7, VIII 8, VIII 9 and VIII 10. The total sample in this study was 32 students of class VIII 1 UPTD SMP Negeri 2 Parepare who were selected using the cluster random sampling technique. The research data was obtained by using a test sheet and a questionnaire sheet. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of the study indicate that there is a positive influence on the use of the wordwall on the mathematics learning outcomes of class VIII UPTD SMP Negeri 2 Parepare students. This is indicated by the mastery of student learning included in the